(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The article is devoted to the formation of a unified multitasking system of risk classification, in order to identify and assess them in general. The article argues that the problem of risk, therefore, lies not in the plane of mathematics, but in its formulation in the subject language. The author puts forward a hypothesis that the unity, integrity and structural and functional complexity of the risk transfer system in insurance activities, risk management and riskology require an adequate approach that would ensure the appropriate perception and study of the object, its functioning and development in the future.